PENGARUH RESILIENSI DAN DUKUNGAN SOSIAL TERHADAP DISTRESS PSIKOLOGIS PADA ORANG DENGAN HIV/AIDS - Siti Nur Hadiyah (Akademi Keperawatan Dharma Husada Kediri, 2020)
Introduction: HIV / AIDS as a disease with a high prevalence, of course, has an impact both physically and psychologically. The negative consequences of the disease and low resilience and social support often cause psychological distress for PLWHA. The purpose of this study is to analyze the effect of resilience and social support on psychological distress in PLWHA and look for the most dominant influential factors. Method: This study is a correlational analytic with a cross-sectional approach. There were 49 respondents taken by using purposive sampling technique. The research instruments used were questionnaires of respondent data and standard instruments that measure psychological distress, resilience, and social support that have been modified and validated. Result: The results showed that resilience and social support significantly affect psychological distress (R2=0,656; p<0.05) and It is known that social support (β = -,539; p<0.05) most dominantly contributes to psychological distress. Discussion: The results of this study concluded that resilience and social support influenced to the psychological distress, and social support is the most dominant factor which affects psychological distress. It is recommended for PLWHA to utilize existing support systems for achieving better mental condition.